Energy conservation through optimal design of cooling towers - Mohiuddin, A. K. M. (1996)
The efficient use of power is more important today than ever before. Much attention is paid nowadays on cooling tower as it is an important resource of energy conservation. Energy conservation is possible only if the tower is designed optimally. In view of optimal design, the author has developed an expert system for the thermal design of wet cooling towers which is based on logic programming. The present expert system is an intelligent program that contains a large body of knowledge concerning wet cooling towers. The system is able to achieve optimal performance in problem solving and thus help conserve energy.